2014
DOI: 10.1094/phyto-11-13-0316-r
|View full text |Cite
|
Sign up to set email alerts
|

Resistance in Mango Against Infection by Ceratocystis fimbriata

Abstract: This study was designed to characterize and describe host cell responses of stem tissue to mango wilt disease caused by the fungus Ceratocystis fimbriata in Brazil. Disease progress was followed, through time, in inoculated stems for two cultivars, 'Ubá' (field resistant) and 'Haden' (field susceptible). Stem sections from inoculated areas were examined using fluorescence light microscopy and transmission and scanning electron microscopy, coupled with energy-dispersive X-ray microanalysis. Tissues from Ubá col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
3
24
0
3
Order By: Relevance
“…A concentração de alguns elementos químicos nos tecidos vegetais pode aumentar a resistência à infecção por patógenos (Haneklaus et al, 2007;Prabhu et al, 2007). Maiores concentrações de S sobre tecidos de caules de cacaueiro e mangueira foram associados com o aumento da resistência, respectivamente, a Verticillium dahliae e a Ceratocystis fimbriata (Cooper et al, 1996;Araujo et al, 2014). O S pode diminuir diretamente a intensidade de diversas doenças pela sua ação antimicrobiana ou, indiretamente, pelo aumento da resistência do hospedeiro (Haneklaus et al, 2007).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A concentração de alguns elementos químicos nos tecidos vegetais pode aumentar a resistência à infecção por patógenos (Haneklaus et al, 2007;Prabhu et al, 2007). Maiores concentrações de S sobre tecidos de caules de cacaueiro e mangueira foram associados com o aumento da resistência, respectivamente, a Verticillium dahliae e a Ceratocystis fimbriata (Cooper et al, 1996;Araujo et al, 2014). O S pode diminuir diretamente a intensidade de diversas doenças pela sua ação antimicrobiana ou, indiretamente, pelo aumento da resistência do hospedeiro (Haneklaus et al, 2007).…”
Section: Discussionunclassified
“…Amostras dos folíolos da terceira folha de 36 plantas (≈ 5 cm 2 ) foram coletadas às 96 hai e processadas de acordo com Araujo et al (2014) para microscopia eletrônica de varredura (MEV) e espectroscopia de raios-X por dispersão em energia (EDS). As amostras foram mantidas em solução de fixativo composto de glutaraldeído 2,5% (v/v) preparado em tampão cacodilato de sódio (0,05 M, pH 7,2) por 7 dias em geladeira a 4 o C. Após essa etapa, o fixativo foi removido, os espécimes foram lavados em tampão cacodilato de sódio (por 15 min, três vezes), pós-fixados em tetróxido de ósmio 0,5% em água por 1 hora e lavados duas vezes por 15 min em água destilada.…”
Section: Microscopia Eletrônica De Varredura E Microanálise De Raios-unclassified
“…X-ray microanalysis also revealed a higher accumulation of S in xylem parenchyma cells, vessel walls, vascular gels, and tyloses, structures in potential contact with hyphae and linked with defense to V. dahlia (Williams et al 2002). Araujo et al (2014b), using X-ray microanalysis, revealed that the tissues of Ubá cultivar (resistance mango wilt) had higher levels of insoluble sulfur than those of Haden cultivar (susceptible).…”
Section: Introductionmentioning
confidence: 94%
“…nicotianae) with high levels of K may be related to the effect of an altered K:Ca ratio on the differential permeability of cell membranes (Prabhu et al 2007). However, Araujo et al (2014b), using X-ray microanalysis, reported that Ca accumulation in stem tissues of mango plants contributed to the strength of the cell walls which hampered C. fimbriata colonization. In the present study, even though the K supply probably affected the K:Ca ratio, due the Ca concentration decrease in the inoculation point, the susceptibility of mango plants against infection by C. fimbriata did not increase.…”
Section: Parameters/variablesmentioning
confidence: 99%